Participation of Women in Post-Earthquake Reconstruction - Pokharel, Ram Raj (Patan Pragya, 2022)
Women's participation in development activities is in a meager condition, if not neglected. There are a lot more to do to accomplish in the path of participation of women in every landscape of society. Thus, the participation of women in post-earthquake reconstruction is a crucial subject at this time. In these circumstances, this study had been initiated. Empowerment is a situation where women have their self-dependency, free mobility, free participation on their own desired sector and field. The meaning of empowerment becomes meaning-ful when women become economically, socially and politically strong. In this regard, this study aims to explore the situation of women’s participation in reconstruction of private households and to establish the key factors that enable or hinder women’s involvement in post-earthquake reconstruction. The study has been based on primary source, data collected from interview schedule by fulfilling the validity from the review of literature with the sample from in Dhunibeshi Municipality Ward No. 2, Dhading The study concludes that the participation of women in the process of post-earthquake reconstruction has-been outstanding. It has great impact on the ideology and the structure of the society. Although it was a rough ride for women to participate actively in reconstruction, their contribution will have been valued in the country's economy and society.